Calibration of parameters for a discrete element model of cotton field residual film-soil mixtures - Li, Jinming; Zhang, Jiaxi; Wang, Yichao; Gao, Zebin; Wang, Xiaoxuan; Shen, Shilong (International Journal of Agricultural and Biological Engineering, 2026)
During residual film recovery operations, the mixing of residual film with soil and the absence of accurate interaction parameters significantly hinder the optimization of key machinery components. To tackle this issue, this study develops a discrete element simulation model based on the Hertz–Mindlin with JKR (Johnson-Kendall-Roberts) contact model, using the residual film-soil mixture as the simulated material. The contact parameters were calibrated through a combination of physical experiments and EDEM simulations. Using Design-Expert software, angle of repose tests and Plackett–Burman experiments were carried out to identify the parameters that have a significant influence on the angle of repose. The optimal set of parameters was determined through steepest ascent and Box–Behnken design (BBD) experiments: residual film–soil rolling friction coefficient 0.61, soil–soil rolling friction coefficient 0.60, soil–steel static friction coefficient 0.68, and soil JKR surface energy 0.46 J/m2. Validation results indicate relative errors of 4.58% for the angle of repose and 2.58% for the uniaxial compressive strength between simulated and measured values. These outcomes offer a useful reference for optimizing residual film recovery equipment and for modeling soil–residual film composite materials. Keywords: cotton fields, residual film-soil mixture, parameter calibration, angle of repose, discrete element method, uniaxial compression test DOI: 10.25165/j.ijabe.20261901.10197 Citation: Li J M, Zhang J X, Wang Y C, Gao Z B, Wang X X, Shen S L. Calibration of parameters for a discrete element model of cotton field residual film-soil mixtures. Int J Agric & Biol Eng, 2026; 19(1): 59–66.